Semarang City Government Policy on Medical Waste Management of Dental Clinics and Independent Practicing Dentists - Pascalin Fiestarika Indraswari; C. Tjahjono Kuntjoro; Yovita Indrayati (Universitas Katolik Soegijapranata Semarang, 2021)
Abstract: The number of dental clinics and dentist independent practices in Semarang city has increased every year. This also increases the potential production of the dental health care waste. They could potentially harm the health care personnel, patients, and also the environment because of their harzardous nature. Therefore, Semarang City Government’s role in regulating and making policies is crucial. This study will not just analyze Semarang City Government policies in managing health care waste in dental clinics and independent dentist practices, but also identify the factors that support or inhibit the implementations.This research was held in Semarang City using sociological juridical approach and presented descriptively and analytically. Primary data was collected through observation and interviews. Secondary legal data is obtained by collecting legal and non-legal theories. In addition, the authors also assess all regulations and policies from central to local governments that are relevant to this topic. The research sample was taken from clinics that run dental services and independent dentist pravtices in Semarang city. The sample was determined by purposive sampling and analyzed qualitatively through analytical naration, graphs and tables.The policies regarding dental health care waste managements in Semarang City are found in the standard operational procedure of licensing. The procedures are held in publishing the operational license for clinics and the professional license for dentists. From a juridical point of view, a legal vacuum regarding obligation of environmental document and overlapping guidelines in both of ministry’s regulation impact both of health care facilities carry out the procedure inappositely. The local government should publish the local guidelines, form letters, or decrees as a quick alternative way to suspend those juridical inhibitions. The licensing procedures act as a sociological support factor for clinic and independent dentist practices to renew their mou with the third parties every year. The lack of knowledge about health care waste ministry’s guidelines inhibit the implementations in those facilities. PDGI Semarang could tahe the role in educating their peers through local seminars or as a material to be discussed at their regular meeting. Technically, the absence of temporary storage and cold srorage make the health care waste unsave to be kept. It is also quite expensive for dentists having cooperation personally with legal third parties. Regarding to these factors, it is wise for local government start planning to build their own hazardous waste management center.Keyword: Policies, Health care waste, Dental service, Clinic, Dentists Abstrak: Potensi produksi limbah medis meningkat seiring dengan bertambahnya jumlah fasilitas pelayanan kesgilut di kota Semarang. Jika tidak dikelola dengan benar, tentu akan berisiko menyebarkan infeksi dan mencemari lingkungan hidup. Pengelolaan limbah medis tidak hanya berkaitan dengan kesehatan dan teknis lingkungan, tetapi juga regulasi yang berlaku. Oleh karena itu, peran Pemkot Semarang sebagai regulator menjadi penting. Penelitian ini bertujuan untuk menganalisis mengenai kebijakan Pemerintah Kota Semarang, pelaksanaan pengelolaan, serta mengidentifikasi faktor pendukung dan penghambat di klinik dan dokter gigi praktik mandiri.Penelitian dilakukan dengan metode yuridis sosiologis dan dipaparkan secara deskriptif analitis. Data primer dikumpulkan melalui studi lapangan dengan cara observasi dan wawacara. Data hukum sekunder diperoleh penulis melalui studi pustaka dengan mengumpulkan teori hokum, regulasi dan kebijakan pemerintah pusat hingga daerah yang relevan, sistem pelayanan kesehatan gigi mulut, serta teknis lingkungan. Sampel penelitian diambil secara purposive dari populasi klinik yang menjalankan pelayanan kesgilut serta dokter gigi praktik mandiri di Kota Semarang. Data penelitian kemudian dianalisis secara kualitatif dan dijelaskan melalui narasi analitis, diagram, dan tabel.Secara umum, kebijakan Pemkot Semarang dalam pengelolaan limbah medis ditemukan di tingkat klinik maupun dokter gigi praktik mandiri. Kebijakan Pemkot Semarang ada dalam bentuk SPO penerbitan izin operasional klinik dan surat izin praktik dokter gigi. Namun, implementasinya terhambat karena terdapat overlapping dari isi pedoman KLHK dengan Kemenkes, serta adanya kekosongan hukum dalam perda lingkungan terkait kategori kepemilikan dokumen lingkungan. Diskresi yang diberikan untuk klinik menjadi tidak tepat karena ada amanah regulasi yang belum terpenuhi. Surat edaran atau surat keputusan Walikota dapat diterbitkan sebagai langkah cepat dalam menyelesaikan hambatan yuridis ini. Pemkot Semarang telah memberikan paksaan administratif bagi klinik berupa kewajiban memiliki dokumen lingkungan dan dokumen kerja sama dengan pihak ketiga. Namun implementasinya di klinik masih menemui hambatan yakni waktu pengangkutan limbah medis oleh pihak ketiga belum sesuai ketentuan. Ketersediaan TPS berizin dan cold srorage di klinik menjadi solusi praktis dari hambatan ini. Pemkot Semarang masih menghimbau dokter gigi praktik mandiri untuk bekerja sama dengan pihak ketiga. Biaya kerja sama dengan pihak ketiga yang relatif mahal menyebabkan dokter gigi enggan bekerja sama. Akan lebih baik jika Pemkot Semarang membangun fasilitas pengelolaan limbah medis untuk mengelola hasil limbah medis yang dihasilkan di wilayahnya.Kata kunci: Kebijakan, Limbah Medis, Kesgilut, Klinik Gigi, Dokter Gigi